2013
DOI: 10.1242/bio.20136106
|View full text |Cite
|
Sign up to set email alerts
|

Significant modulation of the hepatic proteome induced by exposure to low temperature inXenopus laevis

Abstract: SummaryThe African clawed frog, Xenopus laevis, is an ectothermic vertebrate that can survive at low environmental temperatures. To gain insight into the molecular events induced by low body temperature, liver proteins were evaluated at the standard laboratory rearing temperature (22°C, control) and a low environmental temperature (5°C, cold exposure). Using nano-flow liquid chromatography coupled with tandem mass spectrometry, we identified 58 proteins that differed in abundance. A subsequent Gene Ontology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Furthermore, downregulation of the transcription activator STAT2 [54], and EEF1A1, a key participant in translation and regulator of proteolysis, indicates other potential mechanisms for regulating transcription and translation beyond changes in transcription factors. Decreased levels of EEF1A1 protein have also been observed in cold-exposed X. laevis [55] and in winter-acclimatized Rana sylvatica [10].…”
Section: Differential Expression Of Genes Related To Nucleotide and Nmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, downregulation of the transcription activator STAT2 [54], and EEF1A1, a key participant in translation and regulator of proteolysis, indicates other potential mechanisms for regulating transcription and translation beyond changes in transcription factors. Decreased levels of EEF1A1 protein have also been observed in cold-exposed X. laevis [55] and in winter-acclimatized Rana sylvatica [10].…”
Section: Differential Expression Of Genes Related To Nucleotide and Nmentioning
confidence: 80%
“…The conjugation of ubiquitin with target proteins promotes binding to the proteasome and subsequent protein degradation. Protein ubiquitination is transcriptionally enhanced in cold-exposed fish [48,56,57], and frogs [55], possibly due to cold-induced denaturation [57], and may serve as a marker for cold exposure [48]. Protein turnover in cold D. chrysoscelis could supply the cell with amino acids to be used for synthesis of ATP, carbohydrates, and proteins, or these might serve as cryoprotectants [2] or as sources of cryoprotective urea [15].…”
Section: Differential Expression Of Genes Involved In Protein Amino mentioning
confidence: 99%
“…In fact, we previously developed a unique pancytopenic model of X. laevis by exposure to reduced temperatures. In that model, thrombocyte count gradually decreased at 5 C to approximately 60% of the original values [18,19]. However, it was difficult to analyze thrombocyte metabolism owing to lack of specific methods to trace thrombocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The EPOR-expressing erythroid progenitors were observed to localize on the inner wall of the hepatic sinusoids [17]. In addition, we found that X. laevis exposed to low environmental temperature developed acute pancytopenia, including thrombocytopenia [18] with modulation of the hepatic proteome [19]. Thus, X. laevis is a valuable animal model for analysis of hematopoiesis and environmental response.…”
mentioning
confidence: 80%
“…The large size of eggs and embryos, which distinguishes Xenopus frogs from both zebrafish and mouse, at least during the first third of embryonic development, offers one more unique advantage: enough material to perform proteomic analyses with a manageable number of specimens [Nagasawa et al, 2013;Amin et al, 2014;Wühr et al, 2014Peshkin et al, 2015]. With the rapid advance of proteomics, this characteristic will certainly become more prominent in the near future and for example allow comparative interaction studies of wild-type and mutated proteins.…”
Section: The African Frog Xenopusmentioning
confidence: 99%